Money Demand in Guyana - Egoume Bossogo, Philippe (IMF Working Papers; Working Paper ;, 2000)
This paper analyzes broad money demand (M2) in Guyana from January 1990 to September 1999; a period marked by deep transformations aimed at shifting Guyana from a centralized to a market economy. The paper develops a stable error-correction model based on a long-run cointegrating vector of money demand. The latter establishes that real money demand is determined in the long run by real income, interest rates, and the exchange rate. The results also show the existence of strong exchange rate-induced inflation anticipations that are typical to Guyana.